Writing as/about Leisure: Connecting with Oneself and Others through Creative Practice. (19th September 2022) - Griffin, Meridith; Harvey, Kelsey; Gillett, James; Andrews, Gavin
Abstract: Leisure engagement is linked to well-being and social integration, which is important for older adults, who are particularly at risk for social isolation (SI). The aim of this study was to examine the meanings and importance of leisure across the life course. We conducted life history interviews with twenty-six older adults who participated in (primarily) library-based writing programs in Southern Ontario, Canada. We employed narrative inquiry to investigate the processes and outcomes of writing ABOUT leisure. Herein, we highlight the results of one theme from our findings: 'writing AS leisure, ' and two associated sub-themes: 'writing as purposeful leisure: relationship building and social capital' and 'being written out of the story: writing and isolation.' Findings speak to how participants rationalized their involvement in various forms of leisure, and the resultant types and qualities of the social relationships that were enabled and/or inhibited by engagement therein.